Cuidados paliativos na atenção primária: conhecimento dos médicos e enfermeiros da estratégia saúde da família de um município de referência no Maranhão - SANTIAGO, Francisco Alipio de Oliveira (2018)
Introduction: End-of-life care is becoming more frequent due to the progressive aging of the population and the consequent increase in patients with chronic diseases. In Brazil, the few palliative care services are usually linked to specialized hospitals. One of the main obstacles to offering adequate Palliative Care (CP) is the deficiency in the training of health professionals. Objective: to identify the knowledge in Palliative Care and the main fragilities of the daily practices of health professionals of higher level who work in the Family Health Strategy (FHS) in the follow-up of people with illness in the end-of-life. Methods: A cross-sectional, analytical study was carried out at the ESF in the municipality of São José de Ribamar - MA with professionals (doctors and nurses). A German questionnaire (Bonn Palliative Care Knowledge Test) was used to evaluate knowledge and self-confidence in CP. A total of 66 health professionals were interviewed, of whom 30 (45.4%) were physicians and 36 (54.6%) were nurses. For the statistical calculation, SPSS v. 19, assuming a significance level of 0.05. In order to evaluate the correctness and errors of knowledge questionnaires between physicians and nurses, the Chi-square test was used. Results: Variables represented by age, years of schooling, graduation time and working time in primary health care did not differ (p> 0.05). There was a predominance of graduates for over 10 years, with 32 (47.8%). In the care of patients in palliative care, 46 professionals (69.7%) understood the measurement of blood pressure and the measurement of capillary glycemia as the most common practices in FHS. The health professionals evaluated did not have significant differences in the frequency of correct answers, the greatest number of answers obtained was in questions that deal with the physical dimension. There was a higher frequency of better performing physicians in those with graduation time ≤ 5 years and, in turn, a higher frequency of better performing nurses with graduation time ≥ 10 years. Conclusion: Practical assistance and understanding of professionals for patients in CP are predominantly focused on the physical aspects. The professionals express a high profile of self-confidence, however, in an equivocal way with regard to CPs. In short, APS professionals from the Municipality of São José de Ribamar - MA, presented low knowledge regarding Palliative Care and their practices are focused on the control of physical symptoms.